Answer:
![y+5 = \frac{1}{15}(x - 3)}](https://tex.z-dn.net/?f=y%2B5%20%3D%20%5Cfrac%7B1%7D%7B15%7D%28x%20-%203%29%7D)
Step-by-step explanation:
Given
-- Slope
--- Point
Required
Write an equation in point slope form
The point slope form of an equation is:
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
Substitute values for y1, x1 and m
![y-(-5) = \frac{1}{15}(x - 3)}](https://tex.z-dn.net/?f=y-%28-5%29%20%3D%20%5Cfrac%7B1%7D%7B15%7D%28x%20-%203%29%7D)
![y+5 = \frac{1}{15}(x - 3)}](https://tex.z-dn.net/?f=y%2B5%20%3D%20%5Cfrac%7B1%7D%7B15%7D%28x%20-%203%29%7D)
Hence, the equation in point slope form is:
![y+5 = \frac{1}{15}(x - 3)}](https://tex.z-dn.net/?f=y%2B5%20%3D%20%5Cfrac%7B1%7D%7B15%7D%28x%20-%203%29%7D)
45
Mark brainliest please
Hope this helps
Answer:
h(2)+g(2) = -3
Step-by-step explanation:
![h(2) +g(2)\\ \\h(t) = 3-5, g(t) = 2t -5](https://tex.z-dn.net/?f=h%282%29%20%2Bg%282%29%5C%5C%20%5C%5Ch%28t%29%20%3D%203-5%2C%20g%28t%29%20%3D%202t%20-5)
Replace the variable (t) with (
2) in the expression.
h (2) = 3 - 5
Replace the variable (t) with (
2) in the expression.
g(2) = 2(2) -5
Replace the function designators in h(2) +g(2) with the actual functions.
h(t) = 3 - 5 +2 (2) ← plug h(2) into 2(t)
Remove parentheses.
3 - 5 + 2(2)
Multiply 2 by 2
3 - 5 + 4 - 5
Subtract 5 from 3
.
-2 + 4 - 5
Add -2 and 4
2 - 5
Subtract 5 from 2
-3
76.
If the number after the decimal is below five, you round down. If the number is above five, you round up. 76 is your answer.